Religious responses to globalization in Japan: the case of the God Light Association - Whelan, Christal (UMI, 2007)
Abstract: This ethnography examines the impacts of globalization on the emergence, orientation, and transformation of a Japanese New Religion - the God Light Association (GLA) - over the thirty-seven years of its existence. From a popular shamanistic and neo-Buddhist religion where "speaking in tongues" was a central practice, GLA became an increasingly 'rational' and psychologically oriented religion. This shift marked the change in leadership from GLA's founder, Takahashi Shinji, to his daughter, Takahashi Keiko, who sought to attract a growing middle class. These changes reflect a whole generation of "New New Religions" that arose or reached their peak of growth in an era of unprecedented religious pluralism since the mid-1970s. Data for the study include participant observation at GLA's seminars and lectures, weekly attendance at the GLA Kyoto branch study group, archival research, and twenty-four in-depth interviews with members in the elicitation of conversion narratives. The author supplements the case study with comparative field data, based on eighteen months of fieldwork in Japan from 2003-2005, from five additional contemporaneous Japanese New Religions. Japanese new religious movements have arisen in the past 200 years during Japan's transformation from a feudal to a modern society and reflect its encounter with modernity and the West. They function as laboratories for the sampling of new identities, the domestication of alien cultural forms, and the preservation of Japaneseness. They are prime sites for the construction of an alternate modernity---the aspiration to combine the material benefits of modernity with indigenous cultural and religious traditions. This thesis argues that the Japanese New Religions are partially a response to globalization but also to pressures from within Japanese society. The Takahashi's marginalization as members of a socially disadvantaged group of burakumin or "outcastes" increasingly mirrored the anomie of mainstream Japanese. While the existence of New Religions represents a critique of established Buddhism and Shintoism, they are still expected to conform to Japan's broader aesthetic mode of organizing the world. The study demonstrates how this "aesthetic of darkness" was replicated throughout history in various media, and how GLA constructed a counter-aesthetic of light that reflects its modernizing content